Comparison of the ecotoxicological effects of biochar and activated carbon on a marine clam (Meretrix meretrix). (10th April 2018) - Zheng, Hao; Liu, Xia; Liu, Guocheng; Luo, Xianxiang; Li, Fengmin; Wang, Zhenyu
Abstract: Biochar (BC) and activated carbon (AC) amendments have been applied to remediate contaminated sediments because of their benefits in reducing toxicity and/or the bioavailability of contaminants. However, their ecotoxicity to benthic organisms, which are not well understood, should be carefully considered before their practical application. Therefore, a wood-derived BC (WBC) or a coconut shell-derived AC (CAC) was incorporated into a marine sediment at 5% (dw%) to investigate their effects on the growth and nutritional quality of a marine clam ( Meretrix meretrix ). CAC and WBC had no effect on the pH and calcium content of the sediment, but significantly increased the electrical conductivity (EC) and total organic carbon (TOC), and decreased the dissolved organic carbon (DOC). After 28 days of cultivation, WBC reduced the shell growth of the clam by 36.4%, and CAC reduced the soft tissues of the clam by 9.05%. This was probably because WBC and CAC adsorb organic matters and the feeding algae may colonize within their pores, thus, reducing food bioavailability for the clams. Water extracts of CAC and WBC had negligible effects on soft tissue growth, whereas the CAC extract inhibited the growth of clam shells by 57.9%. WBC and CAC had little influence on the nutritional quality of clams, including moisture, crude protein, and crude lipid contents. These findings are helpful to understand the ecotoxicological risks of BC and AC amendments to benthic organisms when used for the remediation of contaminated marine sediments. Graphical abstract: Image Highlights: Ecotoxicity of activated carbon (AC) and biochar (BC) on clams in sediment was compared. BC inhibited shell growth whereas AC decreased soft tissue weight. BC had a limited effect on calm nutritional quality, and AC reduced the ash content of clam. AC extract retarded clam shell growth, whereas BC extract did not affect clam growth.